Improving Fodder Productivity and Quality for Sustaining Livestock - Meena, S. L.; Dass, Anchal (Indian Farming, 2015)
Improved varieties and fodder production technologies of the leguminous forages are available now which may be adopted for enhancing fodder production in the country. A greater attention may be paid to produce more leguminous forages from cultivated crops, rangelands and pastures, top feeds and wastelands to increase livestock productivity and profitability. Besides, NSC, SSC, ICAR Institutes, Agricultural Universities and private seed companies, farmer participatory seed production programme should be encouraged to enhance fodder seed production. Mixed/intercropping of legumes with cereals needs to be promoted, demonstrated and popularized for improving quality, palatability and digestibility of fodder. Healthy fodder will lead to healthy livestock and better quality livestock products.